2021
DOI: 10.33448/rsd-v10i4.14179
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective action of aspirin on Paraquat intoxication in on Drosophila melanogaster

Abstract: Acetylsalicylic acid or aspirin is the most widely used drug globally for its anti-inflammatory characteristics, although little is known about its actions on the central nervous system (CNS). We investigated aspirin's potential neuroprotective effects against paraquat-induced neurotoxicity (PQ) in the present study. Adult male wild-type flies were exposed to a diet containing PQ (3 mM) and/or aspirin (1 μM; 5 μM; 10 μM). Flies fed with PQ reduced locomotion and increased mortality. PQ-induced neurotoxicity ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
2
2
0
Order By: Relevance
“…Our results showed PQ exposition increased the activity of AChE, improved the acetylcholine hydrolysis, and reduced muscular contraction in the muscle cell membranes. Diet supplemented with the P. trifoliata extracts showed a protective effect in AChE activity against damage caused by PQ intoxication, as reported by Carmo et al (2021).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Our results showed PQ exposition increased the activity of AChE, improved the acetylcholine hydrolysis, and reduced muscular contraction in the muscle cell membranes. Diet supplemented with the P. trifoliata extracts showed a protective effect in AChE activity against damage caused by PQ intoxication, as reported by Carmo et al (2021).…”
Section: Discussionsupporting
confidence: 74%
“…In D. melanogaster , the exposition of aspirin (Carmo et al, 2021), omega‐3 (de Oliveira Souza et al, 2017; Souza et al, 2019), saffron methanolic extract (Rao et al, 2016), and Decalepis hamiltonii extracts (Jahromi et al, 2013) showed a protective effect against potential neuronal or muscular damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research, Society and Development, v. 11, n. 17, e148111738931, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i17.38931 12 Additionality, our results showed PQ exposition increased the activity of acetylcholinesterase (AChE), improved the acetylcholine hydrolysis, and reduced muscular contraction in the muscle cell membranes. Diet supplemented with H. sucuuba demonstrated a protective effect in AChE activity against damage caused by PQ intoxication, as reported by Carmo et al (2021).…”
Section: Discussionsupporting
confidence: 59%